Living Hadis Penutupan Lapak Jual Beli Ketika Waktu Shalat di Kampung Madinah Desa Temboro Karas Magetan Jawa Timur - Khamim; Hadziq, Hisbulloh (Tribakti: Jurnal Pemikiran Keislaman, 2020)
One of the interesting phenomena in the "Kampung Madinah" in Temboro Karas Magetan is the tradition of closing shop when the prayer time. The urgency in this research is to review these practices and explain their correlation with the hadith or sunnah of the Messenger of Allah. The research is field research that limits the problem to the application of the value of the sunnah to the tradition of closing shop in the kampung Madinah. The approach used is the sociology of knowledge which implies that reality is socially constructed. The result is that the tradition of closing shop when prayer time is the process of conveying the understanding conveyed by the followers of Jamaah Tabligh through the study of the book Fad}a>il al-A'ma>l which is recited at both bayan and ta'lim. Thus the closing shop when the prayer time is the actualization of the understanding of fiqh inspired by the hadith about the superiority of prayer in congregation.